Human Microbes - The Power Within Health, Healing and Beyond - Appanna, Vasu D. (Springer Singapore, 2018)
This book offers a unique perspective on the invisible organ, a body part that has been visualized only recently. It guides the readers into the world of the microbial constituents that make humans the way they are. The vitamins they produce, the smell they generate, the signals they create, and the molecular guards they elaborate are some of the benefits they bestow on humans. After introducing the notion as to why microbes are an integral component in the development of humans, the book examines the genesis of the microbiome and describes how the resident bacteria work in partnership with the skin, digestive tract, sexual organs, mouth and lungs to execute vital physiological functions. It then discusses the diseases that are triggered by the disruption of the harmonious relationships amongst these diverse systems and provides microbial cures to ailments such as obesity and digestive complications. Finally, the book focuses on the future when the workings of the human microbes will be fully unravelled. Societal changes in health education, the establishment of the microbiome bank, the fight against hunger, space travel, designer traits and enhanced security are explained. Each chapter is accompanied by captivating illustrations and ends with a visual summary. Dr. Appanna has been researching for over 30 years on various aspects of microbial and human cellular systems. He is a professor of biochemistry and has also served as Department Chair and Dean of the Faculty at Laurentian University, Sudbury, Canada. The book is aimed at readers enrolled in medical, chiropractic, nursing, pharmacy, and health science programs. Practicing health-care professionals and continuing education learners will also find the content beneficial.